Yeha, Äthiopien: Forschungen zur Paläoumwelt und Ressourcennutzung - Gerlach, Iris; Weiß, Christian (e-Forschungsberichte des DAI, 2023)
The GeoZentrum Nordbayern, Fachgruppe Paläoumwelt of the University of Erlangen in cooperation with the DAI has conducted sedimentological and ecological investigations in Yeha and its surroundings. These studies are concerned with accumulations of fluvial sediments along recent wadis, which provide data on the climate history during the Holocene. In addition, research focused on the use of natural resources as well as the provenance of building materials employed in the monumental architecture in Yeha. In the case of the latter the wood used to build the palace-like Grat Beʿal Gebri stemmed from the juniper and African olive trees. The stones included phonolite and sandstone from the vicinity of Yeha, limestone quarried at Wuqro, located 80 km from Yeha, and slate from the region of Adua, some 30 km away.